Stable Isotopes Approach to Infer the Feeding Habit and Trophic Position of Freshwater Fishes in Tropical Lakes - Yap, S. K.; I., Muneera; M. I., Syakir; H.H., Zarul; F., Widad (IJEE, 2016)
A study was conducted on the stable isotope variation of muscle tissues from selected freshwater fish species from Temenggor Lake and Chenderoh Lake, Perak, Malaysia from December 2014 to March 2015. The objective is to assess the stable isotopes of δ13C to identify the carbon sources and δ15N of fish species from Temenggor and Chenderoh Lake, Perak, Malaysia to infer the trophic position of these fishes. Four types of fish species were analyzed by using stable isotope approach which were Hampala barb (Hampala macrolepidota), Oxygaster cyprinus (Oxygaster anomalura), Peacock Bass (Cichla ocellaris) and Nile Tilapia (Oreochromis niloticus). Stable isotopes of δ13C and δ15N were analysed using an elemental analyser Thermo Finnigan Flash EA 2000 connected to Finningan DELTA V AVANTAGE plus isotope ratio mass spectrometry by a ConFlo II interface. The δ13C values from both lakes implies a C3 phytoplankton as reported from the literature. Based on δ15N values of fish species, O. anomalura occupies the highest trophic level in Temenggor Lake, reflecting its carnivorous feeding habit despite its small size while C. ocellaris was the highest in Chenderoh Lake, implying its predatory behaviour. Further analysis should be carried out to incorporate primary producers and consumers to elucidate the food web in the tropical lake ecosystem. This study provides a reference record for conducting stable isotopes in the food web of tropical lake ecosystem for better management and deeper understanding of the ecosystem functioning.